Parathyroid Autofluorescence—How Does It Affect Parathyroid and Thyroid Surgery? A 5 Year Experience - Ladurner, Roland (Molecules, 2019)
Injury to parathyroid glands during thyroid and parathyroid surgery is common and postoperative hypoparathyroidism represents a serious complication. Parathyroid glands possess a unique autofluorescence in the near-infrared spectrum which could be used for their identification and protection at an early stage of the operation. In the present study parathyroid autofluorescence was visualized intraoperatively using a standard Storz laparoscopic near-infrared/indocyanine green (NIR/ICG) imaging system with minor modifications to the xenon light source (filtered to emit 690 nm to 790 nm light, less than 1% in the red and green above 470 nm and no blue light). During exposure to NIR light parathyroid tissue was expected to show autofluorescence at 820 nm, captured in the blue channel of the camera. Over a period of 5 years, we investigated 205 parathyroid glands from 117 patients. 179 (87.3%) glands were correctly identified by their autofluorescence. Surrounding structures such as thyroid, lymph nodes, muscle, or adipose tissue did not reveal substantial autofluorescence. We conclude that parathyroid glands can be identified by their unique autofluorescence at an early stage of the operation. This may help to preserve these fragile structures and their vascularization and lower the rate of postoperative hypocalcemia.